Case Report and Review of the Literature: Toxoplasma gondii Encephalitis in a 40-Year-Old Woman with Common Variable Immunodeficiency and a New Diagnosis of Large Granular Lymphocytic Leukemia - Adam Hofmann; Gerasimos Zaharatos; Mark Miller (Canadian Journal of Infectious Diseases and Medical Microbiology)
Toxoplasma gondii has been well-documented to cause central nervous system infections in immunodeficient patients. The present study describes a case of central nervous system toxoplasmosis in a patient with common variable immunodeficiency and newly diagnosed large granular lymphocytic leukemia, with a review of the literature for this association.